1999
DOI: 10.1038/sj.bmt.1701644
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic cystitis: incidence and risk factors in a transplant population using hyperhydration

Abstract: Summary:Haemorrhagic cystitis (HC) is the syndrome of haematuria and symptoms of lower urinary tract irritability in the absence of bacterial infection. We report a low incidence of HC (18.2%) in 681 haemopoietic stem cell transplant patients, using a prophylactic regimen of hyperhydration and forced diuresis. The incidence of grade 3-4 disease is 3.4%. There was a marked difference in incidence between allogeneic and autologous transplant populations, 24.2% vs 3.5% (P Ͻ 0.0005). Busulphan conditioning, acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…1,3,4,10,23,24,28,31,32,37 Older age was identified as a risk factor in pediatric HSCTs, 2,3,31 but no other risk factor has been consistently verified in adult HSCTs, although aGVHD, BU-based conditioning regimens, the type of HSCT and the intensity of conditioning have been suggested. 4,10,23,24,26,30,32 Most recently, Rorije et al 4 reported a single-center, retrospective study. Among 491 allo-HSCT recipients, 78 (15.9%) patients developed BK-HC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4,10,23,24,28,31,32,37 Older age was identified as a risk factor in pediatric HSCTs, 2,3,31 but no other risk factor has been consistently verified in adult HSCTs, although aGVHD, BU-based conditioning regimens, the type of HSCT and the intensity of conditioning have been suggested. 4,10,23,24,26,30,32 Most recently, Rorije et al 4 reported a single-center, retrospective study. Among 491 allo-HSCT recipients, 78 (15.9%) patients developed BK-HC.…”
Section: Discussionmentioning
confidence: 99%
“…HC was graded as follows: grade 1, microscopic hematuria with urinary symptoms; grade 2, macroscopic hematuria; grade 3, macroscopic hematuria with clots; and grade 4, macroscopic hematuria with intervention for clot evaluation and/or urinary retention. 1,25,26 Screening for microscopic hematuria was not routinely performed. Patients with any kind of urinary symptom were evaluated with routine urinalysis and urine culture to rule out bacterial infection.…”
Section: Patients and Allo-sctmentioning
confidence: 99%
“…The prevention of HC includes sufficient oral and parenteral hydration. [7][8][9][10] Hows et al 20 reported a lower incidence of cyclophosphamide-induced HC in marrow transplantation with 2-mercaptoethane sulfonate (mesna). Mesna binds to acrolein, which is responsible for urothelial toxicity as a urinary metabolite of cyclophosmamide.…”
Section: Discussionmentioning
confidence: 99%
“…6 Incidence of BK-virus associated HCis varied across different transplant populations, ranging from 3.6% to 20%, according to definition of HC used. A number of prospective and retrospective case series have investigated risk factors for the development of post-engraftment HC, including myeloablative conditioning, 18 unrelated donor transplants, [19][20][21] and Adenovirus and CMV infection. [22][23][24][25] Demographic risk factors include male sex, 23,26 and age >10 years [27][28][29][30] .…”
Section: Bk-virusmentioning
confidence: 99%